Religion, philosophy and social justice through Christianity GCSE Religious Studies for Edexcel B - Reid, Gordon; Tyler, Sarah K. (Oxford University Press, 2016)
GCSE RS for Edexcel is a brand new course developed in response to real teaching needs for the new 2016 Edexcel specifications and includes resources for both specifications A and B. The series contains 7 student books - print and digital - and 1 Kerboodle exam practice and revision. Student books for this course have been entered into an endorsement process with Edexcel.
Written to match the new 2016 Edexcel B specification
Auch als digitales Schulbuch erschienen
Keywords: Schulbuch